Chemical profiling of erimin-5 pills using GC-MS for active ingredient detection and TLC for dye detection - Latiff, Mohamad Firdaus Abdul (2022)
The abuse of the drug is a never-ending concern for law enforcement authorities all around the world. In Malaysia, Erimin-5 tablets are still being widely abused as can be seen based on the cases reported frequently in the news. These drugs are known to contain nimetazepam or other substituted benzodiazepines. A benzodiazepine is a psychoactive substance that is made up of a benzene ring and a diazepine ring fused together that gives sedative and tranquillizing effects. Many benzodiazepines listed in Schedule IV of the International Convention on Psychotropic Substances 1971 have been classified as controlled substances with a low to moderate potential for misuse and addiction in most countries. It is unknown what types of benzodiazepines are currently used in the formulation of Erimin-5 tablets simply because the clandestine drug chemist can substitute the active ingredients based on their availability as well as use the ingredients which are not controlled by the Dangerous Drug Act. In this study, 50 samples were examined using GC-MS for qualitative study for the presence of active ingredients in Erimin-5 samples. The 50 samples were found to have used different active ingredients where the most common one is etizolam, followed by flualprazolam, nimetazepam, clozapine, 7-aminonimetazepam and alprazolam. For further dye characterisation, 15 samples with sufficient bulk samples were selected for dye profiling using TLC. The dye profiles indicate that most of the samples were of yellow colour, which appeared to be almost similar to the original tablet. Depending on the chemist in the clandestine drug laboratory, different combinations of dyes can be used in producing the tablets. The dyes identified in the examined tablets were tartrazine, sunset yellow and ponceau 4R. In conclusion, forensic profiling was successfully carried out, at least for sample-to-sample comparison. The trend of the most popular benzodiazepines currently used as active compounds is also successfully identified, and certainly, such profiling work shall be conducted from time to time to provide forensic intelligence as well as information for decision-makers.